Measurement of CP asymmetries in two-body B0(s)-meson decays to charged pions and kaons; Physical Review D; Vol. 98, iss. 3 - Aaij R. Roel; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich; Vagner A. R. Aleksandr Rudolfovich (2018, 2018)
Title screen